Gagasan Allah Kristianitas dalam Modernisme, Postmodernisme, dan 'Illative Sense' John Henry Newman - Situmorang, Riston (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2015)
Modern worldview tends to explore everything, including the idea of God, grounded on reason and rational evidences. Postmodernism on the other hand tends to consider that the basic of epistemology of modernism fails to explain the experience and the existence of God, because modernism relies too much on the cognitive and empiric powers. John Henry Newman might be viewed as a constructive postmodernist for he chooses a different power for judging the truth about the concept and experience of God. Newman appears not to think in ‘either-or’ way like in the rationalism and empiricism worldview, but attempts to fuse and bridge the ways of thinking using ‘both-and’. He suggests that this power, i.e., the illative sense, is a faculty that help the believers judge the truth in comprehending the existence of God. With illative sense, people may decide and make spontaneous inferences on concrete issues naturally. In this line, postmodernism might be seen not as a threat or enemy, but companion to religion, for the postmodern epistemology tends to be sensorial, intuitive, and experiential. Illative sense, as a power that each believer has, is converging the particularities towards the existence of God in the context of religious epistemology.